Network Positions and the Probability of Being Acquired: An Empirical Analysis in the Biopharmaceutical Industry. (2nd May 2016) - Mazzola, Erica; Perrone, Giovanni; Kamuriwo, Dzidziso Samuel
Abstract : This paper examines the relationship between the firm's direct ties, its inter‐firm network prominence and its likelihood of being acquired. The authors argue that firm's direct ties and prominence enhance the firm's visibility and signal its quality – and thus foster the firm's likelihood of being acquired. However, higher levels of direct ties and prominence, by providing access to resources and the firm's status, respectively, increase the firm's ability to remain independent and thus reduce its likelihood of being acquired. Thus, the authors posit the overall relation as an inverted U‐shaped. Furthermore, they show that, for firms that undergo an initial public offering, the aforementioned relation becomes much weaker. The hypotheses are empirically tested in the biopharmaceutical industry and important theoretical and managerial implications are discussed.